1 week 1 story Bulletin of School of Information Science UiTM Sarawak: March - October 2024 - Halamy, Suhaida; Ibrahim, Imilia; Ismailly, Norlida; Salji, Mohd Rafiz; Mohd Jawi, Abdul Ismail; Jamil, Nurul Huda Izzati; Abdul Samad, Sabariah; Sulaiman, Sharin; Zaini, Favilla; Jack, Suriani; Haji Bibi, Zainon; Duan, Mohamad Khairul (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
In this issue, we proudly feature an increased contribution of articles from students and the INFORMS Committee, showcasing various perspectives and insights. By documenting the multiple events and activities throughout the semester, One Week One Story transforms from a mere publication into a cherished keepsake of the faculty’s journey. It captures the highlights of stories, projects, and achievements while also serving as a platform to refine writing talent in both creative and academic forms. Not to be forgotten, in appreciation, we proudly celebrate UiTM's 25th anniversary this year, marking a journey of global recognition achieved through dedication, perseverance, and countless achievements. As we reflect on the successes and challenges of the past, we honour our heritage and remain committed to pursuing excellence, embracing new opportunities, and striving to achieve even greater excellence in the future. Thank you UiTM Di Hatiku! Lastly, thank you to all the lecturers and students of the School of Information Science for their enthusiastic contributions to One Week One Story. Your creative efforts have truly enriched this issue. May this spirit of collaboration continue, helping us document and cherish our community's memories. To dear readers, enjoy the journey through these pages!